2014
DOI: 10.1007/s00426-014-0573-5
|View full text |Cite
|
Sign up to set email alerts
|

Aging increases distraction by auditory oddballs in visual, but not auditory tasks

Abstract: Aging is typically considered to bring a reduction of the ability to resist distraction by task-irrelevant stimuli. Yet recent work suggests that this conclusion must be qualified and that the effect of aging is mitigated by whether irrelevant and target stimuli emanate from the same modalities or from distinct ones. Some studies suggest that aging is especially sensitive to distraction within-modality while others suggest it is greater across modalities. Here we report the first study to measure the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
38
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 92 publications
11
38
1
Order By: Relevance
“…Second, our recognition data show that the deviant words were well discriminated from foils. The absence of an effect of the type of deviant word (semantic effect), combined with the presence of distraction by the deviant words relative to standard trials (deviant effect), adds support to the notion that the two effects are independent (see Parmentier, 2014 , for a discussion). Parmentier ( 2008 ) argued that the first effect reflects the time penalty yielded by the involuntary orientation of attention to and away from deviant sounds, while the second results from the involuntary semantic analysis of the deviant sounds.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Second, our recognition data show that the deviant words were well discriminated from foils. The absence of an effect of the type of deviant word (semantic effect), combined with the presence of distraction by the deviant words relative to standard trials (deviant effect), adds support to the notion that the two effects are independent (see Parmentier, 2014 , for a discussion). Parmentier ( 2008 ) argued that the first effect reflects the time penalty yielded by the involuntary orientation of attention to and away from deviant sounds, while the second results from the involuntary semantic analysis of the deviant sounds.…”
Section: Discussionmentioning
confidence: 91%
“…Task-irrelevant stimuli that unexpectedly differ from an otherwise structured or repeated sequence of stimuli (deviant among standard stimuli) capture attention and yield behavioral distraction in an unrelated ongoing task (e.g., Bendixen et al, 2010 ; Escera, Alho, Winkler, & Näätänen, 1998 ; Parmentier, 2014 ; Parmentier, Vasilev, & Andrés, 2018 ; Schröger, 1996 ; Schröger & Wolff, 1998b ; Vasilev, Parmentier, Angele, & Kirkby, 2018 ). While this type of effect has been reported across various sensory modalities (e.g., Berti, 2008 ; Berti & Schröger, 2003 ; Boll & Berti, 2009 ; Li, Parmentier, & Zhang, 2013 ; Ljungberg, Parmentier, Leiva, & Vega, 2012 ; Parmentier, 2016 ; Parmentier, Ljungberg, Elsley, & Lindkvist, 2011 ; Roeber, Widmann, & Schröger, 2003 ), the phenomenon has been most abundantly studied with auditory distractors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lutfi-Proctor et al re-designed the conventional Stroop test for an audio-visual version and found that auditory interference (i.e., semantics or phonetics distraction) heavily deteriorated the visual task performance [ 37 ]. Interestingly, Leiva et al [ 38 ] examined the saliency of auditory interference in the different age groups, demonstrating that the elderly seemed to show an audio-sensitivity effect in the cross-modal task but not in the unimodal task. More recently, Stothart and Kazanina [ 39 ] conducted an event-related potential (ERP) study to examine peripheral and cortical involvement of auditory interference between different age groups.…”
Section: Introductionmentioning
confidence: 99%
“…At the behavioral level, deviant sounds delay (and sometimes reduce the accuracy of) responses to target stimuli (see Parmentier, 2014, for a conspectus of behavioral deviance distraction studies), whether presented in uni-modal auditory (e.g., Berti andSchröger, 2003, 2004;Schröger, 1996) or visual tasks (Berti and Schröger, 2004;Boll and Berti, 2009;Grimm et al, 2009), or in cross-modal oddball tasks where an irrelevant stimulus in one sensory modality precedes a target stimulus in another (auditory-visual: Andrés et al, 2006;Boll and Berti, 2009;Escera et al, 1998Escera et al, , 2001Leiva et al, 2014aLeiva et al, , 2014bLi et al, 2013;Mayas et al, 2014;Parmentier and Andrés, 2010;SanMiguel et al, 2010;van Mourik et al, 2007;Wetzel et al, 2009;tactile-visual: Parmentier et al, 2011).…”
mentioning
confidence: 98%